2016
DOI: 10.1083/jcb.201609101
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophil mechanotransduction: A GEF to sense fluid shear stress

Abstract: Philipp Niethammer highlights work from the Rottapel group exploring the role of the GEF-H1 protein in shear- sensing by neutrophils.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 15 publications
1
12
0
Order By: Relevance
“…Dixit et al (23) hypothesized that shear forces used high-affinity LFA-1 transmission to facilitate the cooperation with the calcium release-activated channel Orai1 in directing localized cytoskeletal activation and subsequent directed migration. Besides, Artemenko et al 35 or Niethammer (44,48) have shown that flow could activate internal signalling networks common with chemotaxis. These works support therefore the hypothesis that leukocyte flow guiding may be mediated by active signal transduction and processing, like for chemotaxis, but the mechanistic link between mechanotransduction and mechanotaxis is not fully established.…”
Section: Discussionmentioning
confidence: 99%
“…Dixit et al (23) hypothesized that shear forces used high-affinity LFA-1 transmission to facilitate the cooperation with the calcium release-activated channel Orai1 in directing localized cytoskeletal activation and subsequent directed migration. Besides, Artemenko et al 35 or Niethammer (44,48) have shown that flow could activate internal signalling networks common with chemotaxis. These works support therefore the hypothesis that leukocyte flow guiding may be mediated by active signal transduction and processing, like for chemotaxis, but the mechanistic link between mechanotransduction and mechanotaxis is not fully established.…”
Section: Discussionmentioning
confidence: 99%
“…Brief exposure to high shear sensitizes platelets to activation under subsequent low insult shear, so it is reasonable to presume leukocytes might be affected the same way ( 36 ). It has been suggested that shear stress activates leukocytes through structural changes rather than ligand-induced signal transduction ( 37 ). Interestingly, repeated mechanical deformation at 25 dynes/cm 2 of primed neutrophils can return them to a resting state ( 38 ), but above this leads to structural disruption ( 39 ).…”
Section: Inflammation In Response To Ventricular Assist Devicesmentioning
confidence: 99%
“…Shear stress affects neutrophils independently of biomaterials as evidenced by increased activation of granulocytes in HMII patients compared to the HVAD (35). It is suggested that the physical forces of non-physiological shear stress cause structural changes that activate granulocytes (65). Activation is marked by an increase in MAC-1 expression as observed in the HMII patients (35).…”
Section: Resultsmentioning
confidence: 95%
“…GEF-H1 is activated in response to shear stress to promote spreading, crawling, and transmigration of neutrophils (61). Depolymerised GEF-H1 re-localises to the uropod to stimulate Rho signalling resulting in intracellular tension and cellular contractility (65).…”
Section: Innate Immune Cellsmentioning
confidence: 99%
See 1 more Smart Citation